(untitled) (Shiksha Shastra Saurabh, 2025)
The perception, career aspirations and experience of Master of Education (M. Ed.) graduates have been examined in relation to employability issues in this study. The research has addressed perception in relation to the curriculum provided to M. Ed. students, drawing on the Human Capital Theory put forward by Becker (1964) and Yorke (2006). Adopting a mixed-methods approach, quantitative data were collected through a self-administered questionnaire from conveniently sampled respondents while qualitative data were generated through focus group discussion with 30 graduates (18 females, 12 male) from Kathmandu Shiksha Campus (KSC) and semi-structured interview was also heldwith six purposively selected students. The qualitative data were analyzed thematically with a focus on employability related issues. The findings show that the M.Ed. programme under Tribhuvan University performs well in research training and academic relevance with 53.3% positive responses. However, the data indicate serious limitations in teaching practice, professional skill development, mentorship and most critically responsiveness to the job market demands with 96.7% of respondents. Although participants perceived the pedagogy as relevant to the academic sector, they reported a mismatch between their career aspirations, the skills required during the programme and the requirements of academia and the broader job market. Furthermore, inconsistencies have been identified between TU-prescribed curriculum and Teacher Service Commission requirements. The curriculum was perceived as overly theoretical and insufficiently aligned with contemporary workforce demands. Overall, the findings suggest an urgent need to strengthen the employability orientation of the M.Ed. Programme to meet graduates’ aspirations and institutional requirements. This study points out some notable gaps in the existing curriculum and provides a basis for further research to enhance the employability of M.Ed. graduates in Nepal.